2022
DOI: 10.3389/fmed.2022.943112
|View full text |Cite
|
Sign up to set email alerts
|

A survey of Australian and New Zealand medical parents' experiences of infertility, pregnancy, and parenthood

Abstract: ObjectiveTo describe the incidence of infertility, pregnancy complications, and breastfeeding practices among Australian and New Zealand doctors and identify factors associated with increased pregnancy complication rates.MethodsA survey of ANZ doctors using an online questionnaire during November 2021.ResultsOne thousand ninety-nine completed responses were received. The median age of female doctors at the time of their first child was 32.4. Fertility testing was undertaken by 37%, with 27% having in vitro fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Expanding on a number of survey‐based studies, a recent Canadian cohort study found physicians delayed childbearing relative to the general population, with rapidly increasing fertility rates upon completing specialisation, thus concentrating pregnancies during AMA 9 . Although not without limitations, an Australasian survey study found female doctors tended to have fewer children and at a later age than both male doctors (and their female partners) and the general population at an average age of 32.4 years for female doctors compared with 29.4 years for the Australian national average 10 …”
Section: Competing Interestsmentioning
confidence: 99%
See 3 more Smart Citations
“…Expanding on a number of survey‐based studies, a recent Canadian cohort study found physicians delayed childbearing relative to the general population, with rapidly increasing fertility rates upon completing specialisation, thus concentrating pregnancies during AMA 9 . Although not without limitations, an Australasian survey study found female doctors tended to have fewer children and at a later age than both male doctors (and their female partners) and the general population at an average age of 32.4 years for female doctors compared with 29.4 years for the Australian national average 10 …”
Section: Competing Interestsmentioning
confidence: 99%
“…A systematic review and meta‐analysis found low‐grade data that suggests fixed nightshifts and working more than 40 h per week are associated with increased risk of miscarriage 14 . Experiences of pregnancy loss were reported by 36.4% of surveyed Australasian physician parents, with 37% undergoing fertility testing and one in four requiring assisted reproductive technology 10 . The paper by Thomson and McIlwaine in this series shares both the procedural and personal experiences of assisted reproductive technology, which may be especially relevant for trainees considering fertility preservation options 15 …”
Section: Competing Interestsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nearly half (49.5%) were female 1 . In a survey by Kevric et al ., 2 the median age of female doctors in Australia and New Zealand having their first child is 32.4 years. Therefore, a large proportion of trainees have likely already started a family or plan to during training.…”
Section: Competing Interestsmentioning
confidence: 99%